A comparative study of earnings quality of firms listed in the NEEQ market and the Growth Enterprise Market. Issue 4 (2nd October 2018) - Yuan, Hongqi; Kong, Desong; Zhang, Chujun; Chen, Chao
ABSTRACT: This paper explores the differences in earnings quality between the National Equities Exchange and Quotations (NEEQ) companies and the Growth Enterprise Market (GEM) companies. The study finds that NEEQ companies and GEM companies have different characteristics in earnings quality. NEEQ companies have a significantly higher level of upward earnings management than GEM companies, while GEM companies have stronger incentives to manage earnings downward through a 'big bath' than NEEQ companies, owing to the special treatment and delisting regulations for GEM firms. We also find that the unique institutions of NEEQ have significant impacts on the earnings quality of companies. Innovation-layer companies, companies applying for IPOs, companies with independent directors, companies trading with market makers, companies with private equity (PE) or venture capital (VC) investment have higher earnings quality.